Edukasi dan Pelatihan Terbimbing Bagi Guru Mengenai Pembelajaran Secara Daring Sebagai Upaya Pencegahan Covid-19 - Erniwati, Erniwati; Anas, Muhammad; Hunaidah, Hunaidah (Universitas Nusantara PGRI Kediri, 2021)
Integrated community service activities KKN-Tematik are a forum for educating and training teachers and students using online learning as an effort to prevent Covid-19 with the purpose that teachers can carry out learning activities by online learning with utilizing several applications such as WhatsApp, Google Classroom, Google meet, and zoom. The activities on the work program KKN-Tematik begins with socialization to teachers in the location of each student, followed by educating and guided training on online learning methods and the use of several applications that can be used, as well as conducting trials involving several students. This activity received positive responses from the teacher with the seriousness and activeness of the teacher to find out the use of applications in online learning which so far has only limited to the use of WhatsApp through questionnaires. In addition, the ability and skills of teachers regarding the use of several applications have increased from the inability to use applications in online learning to be able to use these applications with the readiness of teachers to carry out online learning in the future. However, some of the barriers experienced by the teacher in the implementation of online learning are not yet maximal inability, so they still need further independent guidance and insufficient advice and infrastructure such as internet networks, data packets, and not all students have cellphones